(untitled) (Experimental and Applied Veterinary Research Journal, 2025)
Background: Augmentin is a common antibiotic that can cause liver injury. It increases oxidative stress and damages liver cells. N-acetylcysteine (NAC) is known for its antioxidant and protective effects on the liver. This study aimed to evaluate the protective role of NAC against augmentin-induced liver damage in rats by measuring biochemical markers, oxidative stress indices, lipid profile, and histopathology. Methodology: Forty male rats were divided into four groups (10 each). Control group received basal diet. T1 received augmentin (30 mg/kg/day). T2 received NAC (150 mg/kg/day). T3 received NAC plus augmentin at the same doses. Oral treatments lasted for 5 weeks. Blood samples were collected for biochemical tests (liver function enzymes and lipid profile). Results: The animals of T1 group showed a significant (p < 0.05) rise of liver enzymes, and lipid profile parameters, and a decrease in HDL, total protein and albumin as compared with the control. While T2 depicted a significant correction of these alterations toward the control values (p < 0.05). T3 explained a significant improvement in liver enzymes, lipid profile, and bilirubin, approaching control levels (p < 0.05). Conclusions: NAC effectively reduced augmentin-induced biochemical and histological liver damage. It has antioxidant, anti-inflammatory, and lipid-stabilizing effects. NAC may be considered as a supportive therapy in drug-induced hepatotoxicity.